Formulas to Explain Popular Oscillometric Blood Pressure Estimation Algorithms - Chandrasekhar, Anand; Yavarimanesh, Mohammad; Hahn, Jin-Oh; Sung, Shih-Hsien; Chen, Chen-Huan; Cheng, Hao-Min; Mukkamala, Ramakrishna (Frontiers in Physiology, 2019)
Oscillometry is the blood pressure (BP) measurement principle of most automatic cuff devices and may potentially be extended to achieve cuff-less BP monitoring. The oscillogram (blood volume oscillation amplitude-external pressure function) is measured, and BP is then estimated via an empirical algorithm. The objective was to establish formulas to explain popular empirical algorithms. A mathematical model of the oscillogram was developed and analyzed to derive parametric formulas for explaining the maximum amplitude, derivative, and fixed ratio algorithms. Exemplary parameter values were obtained by fitting the model to measured oscillograms. The model and formulas were validated by showing that their predictions correspond to measurements. The formula for the maximum amplitude algorithm indicates that it yields a weighted average of systolic and diastolic BP (0.45 and 0.55 weighting) instead of commonly assumed mean BP. The formulas for the derivative algorithm indicate that it can accurately estimate systolic and diastolic BP (<1.5 mmHg error), if oscillogram measurement noise can be obviated. The formulas for the fixed ratio algorithm indicate that it can yield inaccurate BP estimates, because the ratios change substantially (over a 0.5-0.6 range) with arterial compliance and pulse pressure and error in the assumed ratio translates to BP error via large amplification (>40). The established formulas allow for easy and complete interpretation of perhaps the three most popular oscillometric BP estimation algorithms while providing new insights. The model and formulas may provide a foundation for improving the accuracy of both automatic cuff and cuff-less BP measurement devices.